Movie as a Social Critique Symbol of Polygamy: A Semiotic Analysis of “Berbagi Suami” Movie - Rintis Dyah Kusumawati (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2010)
Within man-woman relations contexts, polygamy is still pros and cons. Based on the Holy Qur’an, polygamy can be tolerated by additional note if they can behave equal and in just. But the others said that the practice of polygamy is manifestation to marginalize a woman. Polygamy can open the violence toward woman more frequently than monogamy at any level of aspects. Movie “Berbagi Suami” depicts this situation. It seems to illustrating that polygamy raises some problems for woman within the domestic life especially within man-woman relations contexts. Starting point from this view, this is to analyze the “Berbagi Suami” Movie by applying the Barthes’s semiology. By Barthes’s method, “Berbagi Suami” movie was scrutinized into two level of analysis. The results was found that Berbagi Suami Movie echoed the voice of critism through woman perspectives albeit not completely. This film also principally brought polygamy into discourse to audience and let them to judge the discourse.